Tansport processes controlling uranium uptake by plants - Darmovzalova, Jana (Cranfield University, 2018)
The mechanisms of uranium (U) uptake by plants growing in contaminated soils are poorly understood, constraining the development of mitigation measures and models of U fate and behaviour. Uptake involves a complex interaction between diffusion and reaction processes in the rhizosphere, and root-induced changes in the soil affecting these processes. This thesis is concerned with developing better understanding of these processes, as represented in predictive mathematical models. Most past research on U transport and reaction in soils has been in shaken suspensions or flow-through systems, in which the rate-limiting processes are artificially altered. This thesis develops a novel experimental approach in which diffusion and reaction are measured simultaneously in soil with stationary pore water, better representing the rhizosphere. Concentration- distance profiles of U were measured between two half-cells of soil, one of which initially contained U and the other not, giving rates of desorption in the source and adsorption in the sink cell. The effects of typical root-induced changes in soil pH and CO₂ pressure were measured. Two models were compared: (a) an analytical solution of the appropriate diffusion equation with a constant diffusion coefficient, and (b) a numerical solution allowing for time- and concentration-dependent diffusion. The model parameters were measured or otherwise estimated independent of the concentration-distance profiles. The simple analytical solution correctly accounted for the effects of pH and CO₂ pressure on U diffusion, but under-predicted the diffusive flux. The numerical model correctly predicted the flux and concentration-distance profiles, including a discontinuity at the source-sink boundary due to differences in the kinetics of desorption and adsorption. The results show the importance of correctly allowing for the effects of pH, CO₂ pressure and sorption kinetics in modelling U uptake by plant roots. The model should be further corroborated in mesocosm, half-cell and field experiments, and by verifying U speciation.
Keywords: Diffusion; uranium; soil modellling; radionuclide uptake; rhizosphere processes; reaction processes